Meningkatkan Kemampuan Membaca Kata Berpola KV-KVK Melalui Media Book Creator Bagi Murid Disabilitas Rungu (Single Subject Research Kelas IV di SLBN 1 Kubung) - Venny Adelia Contesa; Zulmiyetri Zulmiyetri; Damri Damri; Syari Yuliana; Rila Muspita (PEDAGOGIC: Indonesian Journal of Science Education and Technology, 2026)
The ability to read words with a CV-CVC pattern is one of the challenges for students with hearing disabilities because limited sound perception can cause difficulties in recognizing and producing phonemes, especially final consonants. This condition was found in a fourth-grade student with hearing disabilities at SLBN 1 Kubung who had difficulty reading words with a CV-CVC pattern correctly. This study aims to describe the improvement in the ability to read words with a CV-CVC pattern through the use of Book Creator media. The study used a quantitative approach with the Single Subject Research (SSR) method with an A-B-A design. Data were collected through performance tests and analyzed using visual analysis within and between conditions. The results showed an increase in reading ability from the initial condition with a score of 30% to 80% after intervention using Book Creator media, and this ability could be maintained in the final baseline phase. These findings indicate that Book Creator media can be an alternative visual learning media that supports more interesting and structured reading practice for students with hearing disabilities. This study provides practical implications for teachers in selecting visual-interactive-based media to help develop literacy skills for students with hearing impairments